Delirium in the Intensive Care Unit - Jeong-Ho Hong (Journal of Neurocritical Care, 2015)
Delirium is a cognitive disturbance with acute onset or fluctuating clinical course. It is recognized as one of the most common complications in the intensive care unit (ICU). The impact of delirium in the ICU on mortality, hospital or ICU length of stay, cost burden and post-ICU cognitive impairment is well documented. Although the underlying pathophysiology is poorly understood, numerous predisposing and precipitating risk factors for delirium are suggested. Prevention strategy, early detection using screening tools, and control of the underlying causes are crucial to improve clinical outcomes of delirium. Pharmacological treatment such as antipsychotics may also be considered as a treatment option, although its efficacy and safety are not yet established. The purpose of this review was to provide an overview of clinical characteristics, risk factors and treatment for delirium in the ICU.